Exploring Metaphor Use: Its Categories and Translation Strategies within the Novel Anak Bajang Menggiring Angin by Sindhunata into Herding the Wind by Joan Suyenaga - Ani Maghfiroh; Erna Andriyanti (Masyarakat Linguistik Indonesia, 2021)
This research explores the use of metaphor categories and its translation strategies using the theory of Newmark (1988). The qualitative method was employed since the data were in the form of verbal data derived from novels. In the stage of collecting the data, an observational method followed by note-taking technique was applied. As indicated in the section of results and discussion, 151 data were considered to be metaphor in the ST whilst 90 data belong to TT and 61 other data were converted into other forms (simile, sense, and even deletion). Of six metaphor categories, four categories emerged in the texts whereas two out of them (Adapted and Recent metaphor) were not used. The metaphor category most dominantly used in both texts is dead metaphor with 111 data (11,2 %) in the ST and 70 data (7,8 %) in the TT whilst the strategy ‘metaphor to metaphor’ dominates over other strategies (81 data, 53,6 %). Meanwhile, the least strategy employed was ‘metaphor to simile with sense’ and strategy ‘metaphor to metaphor plus sense’ is disregarded. In addition, as the metaphor translation strategies were bound to the metaphor categories, the result poses that dead metaphor is the category translated by using the strategy ‘metaphor to metaphor’ in most frequency.